A Field Study on Small Accounting Firm Membership in Associations and Networks: Implications for Audit Quality - Bills, Kenneth L.; Hayne, Christie; Stein, Sarah E. (The Accounting Review, 2018)
ABSTRACT Small accounting firms represent important participants in the audit market, yet details of how they operate and develop competencies remain unexplored. Small firms often join forces through accounting associations and networks (AANs), which may help them overcome significant challenges commonly faced by smaller firms. We interview 37 partners from 18 firms representing nine AANs to examine how small firms leverage their AAN membership and to understand the related implications for audit quality. Our findings indicate that small firms acquire needed resources and enhance their market legitimacy through AAN membership; however, the nature and extent to which they do so varies by AAN type. Importantly, we also find that the majority of respondents perceive AAN resources, especially access to expertise, as critical to their firms' audit quality. Our research, informed by a theoretical lens based on resource dependence and legitimacy, enriches existing auditing literature, provides a new perspective for member firms and regulators, and responds to recent calls to understand factors affecting accounting firms' competencies.